New species of Steleops (Psocodea: ‘Psocoptera’: Psocidae) from Brazil, Colombia, Mexico and Peru - Obando, Ranulfo González; Aldrete, Alfonso N. García; Carrejo, Nancy Soraya (Zootaxa, 2011)
Ten species of neotropical Steleops Enderlein, are described and illustrated. A key to the neotropical species of the genus is provided, with comments on the affinities of the new species. The location of the types is indicated with each description.